2007
DOI: 10.3732/ajb.94.4.683
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of Vriesea gigantea Gaud. (Bromeliaceae) in southern Brazil

Abstract: Plant fertility is a central subject of many questions in plant evolutionary and conservation biology. Pollen availability, abiotic resources, and flowering pattern can limit fruit and seed production. Open pollination and pollen supplementation studies are used to estimate any pollen limitation in natural populations. To study the impact of these factors on the reproductive success of Vriesea gigantea, an epiphytic bromeliad in the Atlantic Rainforest in Brazil, its fertility in four natural populations in It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 38 publications
1
53
0
4
Order By: Relevance
“…Th e larger production of fruits and seeds may be also aff ected by pollinator behavior since bromeliads in sunny places were visited more oft en. Pollinator foraging may be infl uenced by the environmental light (Kilkenny & Galloway, 2008) and pollen limitation due to reduced pollinator visits may cause the variation in reproduction among bromeliad populations (Paggi et al 2007). Since hummingbirds are very sensitive to environmental changes in resource supply (Cotton 2007) and avoid unrewarding patches (Sandlin 2000), they may have visited the bromeliads in sunny patches more oft en due to greater fl ower availability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Th e larger production of fruits and seeds may be also aff ected by pollinator behavior since bromeliads in sunny places were visited more oft en. Pollinator foraging may be infl uenced by the environmental light (Kilkenny & Galloway, 2008) and pollen limitation due to reduced pollinator visits may cause the variation in reproduction among bromeliad populations (Paggi et al 2007). Since hummingbirds are very sensitive to environmental changes in resource supply (Cotton 2007) and avoid unrewarding patches (Sandlin 2000), they may have visited the bromeliads in sunny patches more oft en due to greater fl ower availability.…”
Section: Discussionmentioning
confidence: 99%
“…Selfi ng has been found in most species and in several genera, including Aechmea, Alcantarea, Billbergia, Canistrum, Pitcairnia and Vriesea (Martinelli 1997;Siqueira Filho & Machado 2001;Wendt et al 2001;Wendt et al 2002;Lenzi et al 2006;Paggi et al 2007), yet incompatibility systems are also found in Aechmea, Billbergia and Quesnelia (Martinelli 1997;Canela & Sazima 2003). Spatial and temporal mechanisms to avoid selfi ng include dichogamy, dioecy and herkogamy (Martinelli 1997;Siqueira Filho & Machado 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have started to use species of the closely related genera, Vriesea and Alcantarea, for studies of the genetic underpinnings of adaptive radiation in the Tillandsioideae subfamily of Bromeliaceae. These two genera have diversified into multiple species adapted to life in continuous forest or on granitic 'inselberg' rock outcrops in the South American Atlantic Rainforest (Barbará et al, , 2008Paggi et al, 2007;Palma-Silva et al, 2007). This study provides vital genetic and phylogeographic data to inform ongoing studies on the genetics of population divergence and speciation in this group.…”
Section: Introductionmentioning
confidence: 99%
“…1600 km between the Brazilian states of Rio Grande do Sul (RS) and Espírito Santo (ES) (Figure 1; Smith and Downs, 1977). The species has a mixed-mating system (Paggi et al, 2007) with bat pollination (Sazima et al, 1999) and wind-based seed dispersal. Its populations are generally large and composed of patches of different sizes and densities.…”
Section: Introductionmentioning
confidence: 99%